Highly sensitive molecular assay based on Identical Multi-Repeat Sequence (IMRS) algorithm for the detection of Trichomonas vaginalis infection - Clement Shiluli; Shwetha Kamath; Bernard N. Kanoi; Racheal Kimani; Bernard Oduor; Hussein M. Abkallo; Michael Maina; Harrison Waweru; Moses Kamita; Nicole Pamme; Joshua Dupaty; Catherine M. Klapperich; et al. (PLoS ONE, 2025)
Introduction Annually, approximately 174 million people globally are affected by Trichomonas vaginalis (T. vaginalis) infection. Half of these infections occur in resource-limited regions. Untreated T. vaginalis infections are associated with complications such as pelvic inflammatory disease and adverse pregnancy outcomes mostly seen in women. In resource-limited regions, the World Health Organization (WHO) advocates for syndromic case management. However, this can lead to unnecessary treatment. Accurate diagnosis of T. vaginalis is required for effective and prompt treatment. Molecular tests such as Polymerase Chain Reaction (PCR) have the advantage of having a short turn-around time and allow the use of non-invasive specimens such as urine and vaginal swabs. However, these diagnostic techniques have numerous disadvantages such as high infrastructure costs, false negative and positive results, and interstrain variation among others. This study aimed to evaluate the use of identical multi-repeat sequences (IMRS) as amplification primers for developing ultrasensitive diagnostic for T. vaginalis. Methods We used genome-mining approaches based on identical multi-repeat sequences (IMRS) algorithm to identify sequences distributed on the T. vaginalis genome to design a primer pair that targets a total of 69 repeat sequences. Genomic T. vaginalis DNA was diluted from 5.8×102 to 5.8×10−4 genome copies/μl and used as a template in the IMRS-based amplification assay. For performance comparison, 18S rRNA PCR assay was employed. Results The T. vaginalis -IMRS primers offered a higher test sensitivity of 0.03 fg/μL compared to the 18S rRNA PCR (0.714 pg/μL). The limit of detection for the Isothermal assay was 0.58 genome copies/mL. Using real-time PCR, the analytical sensitivity of the T. vaginalis -IMRS primers was <0.01 pg/μL, equivalent to less than one genome copy/μL. Conclusion De novo genome mining of T. vaginalis IMRS as amplification primers serves as a platform for developing ultrasensitive diagnostics for Trichomoniasis and a wide range of infectious pathogens.